Short Communication: Peanut introduced germplasm response against Ralstonia bacterial wilt disease - NOVITA NUGRAHAENI; MUJI RAHAYU (Nusantara Bioscience, 2017)
Nugrahaeni N, Rahayu M. 2017. Short Communication: Peanut introduced germplasm response against Ralstonia bacterial wilt disease. Nusantara Bioscience 9: 138-140. Peanut germplasm introduction is a means to increase genetic variability within the germplasm collection. However, its utilization is frequently hampered by its susceptibility to bacterial wilt disease, the main disease in peanut cultivation in Indonesia. The aim of the present study was to assess peanut introduced germplasm response against Ralstonia bacterial wilt disease. One hundred and fifty peanuts introduced germplasm were planted on the bacterial wilt endemic area in Pati, Central Java, Indonesia. Pre-planted isolation revealed that the bacterial population in the soil was considered high, i.e. 2.6x106 cfu.g-1. The trial was laid out in RCBD, replicated two times. Each accession was planted in two rows of 4-m length with 40 cm x 10 cm plant spacing. The crop received a basal dose of Phonska at 300 kg.ha-1 and SP36 at 100 kg. ha-1. Observations were made on bacterial wilt disease incidence and agronomic traits. Research result showed that the introduced germplasm was highly variable in their responses to the wilt disease with wilt incidence ranging from 0% to 100%. Twenty-three accessions, out of 150, were resistant to the disease. Those resistant accessions showed good agronomic characters and gave dry pod yield in the range of 1.56-4.5 t.ha-1. This results indicated that introduced germplasm could be used in increasing variability of bacterial wilt resistant gene source as well as in increasing yield potential in developing new peanut improved cultivars.